2024
DOI: 10.26599/fshw.2022.9250216
|View full text |Cite
|
Sign up to set email alerts
|

Alleviatory effect of isoquercetin on benign prostatic hyperplasia via IGF-1/PI3K/Akt/mTOR pathway

Young-Jin Choi,
Meiqi Fan,
Nishala Erandi Wedamulla
et al.

Abstract: We evaluated the effect of isoquercetin (quercetin-O-3-glucoside-quercetin, IQ) as a functional component of Abeliophyllum disistichum Nakai ethanol extract (ADLE) on prostate cell proliferation and apoptosis and its effects on the IGF-1/PI3K/Akt/mTOR pathway in benign prostatic hyperplasia (BPH). Metabolites in ADLE were analyzed using UHPLC-qTOF-MS and HPLC. IQ was orally administered (1 or 10 mg/kg) to a testosterone propionate-induced BPH rat model, and its effects on the prostate weight were evaluated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The activation of the PI3K signalling pathway phosphorylates AKT, increasing cell survival and decreasing apoptosis [ 28 ]. Significantly elevated levels of phosphorylated AKT and PI3K gene expression were observed in prostate tissue from BPH patients [ 29 ]. Our results revealed that FAK and the PI3K/Akt signalling pathway were downregulated in RWPE-1 cells after avellanin A intervention, significantly reducing cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the PI3K signalling pathway phosphorylates AKT, increasing cell survival and decreasing apoptosis [ 28 ]. Significantly elevated levels of phosphorylated AKT and PI3K gene expression were observed in prostate tissue from BPH patients [ 29 ]. Our results revealed that FAK and the PI3K/Akt signalling pathway were downregulated in RWPE-1 cells after avellanin A intervention, significantly reducing cell survival.…”
Section: Discussionmentioning
confidence: 99%